Advancing Student Self-Understanding through Classical Career Guidance at Laboratory Senior Highschoool UM - Harits, Iasha Brillianti; Muslihati, Muslihati; Pratama, Ari Yoga; Hanafi, Husni (Universitas Negeri Malang, 2024)
Initial observations indicate that many students in Laboratory Senior Highschool UM struggle with their self-awareness, hindering their career planning. They face challenges in identifying their hobbies, talents, interests, potential, and abilities, which are crucial for career decision-making. This study aims to enhance self-awareness among students through career guidance services at Laboratory Senior Highschool UM. This research using a quantitative quasi-experimental approach with a One Group Pretest-Posttest design. This research involved 31 students, which were purposively selected as the sample. Initial findings revealed that 9 students had low self-awareness scores on the pretest, while the others had moderate levels. Post-intervention results showed an improvement from low-moderate to moderate-high self-awareness, with an average posttest score of 42. This study demonstrates that career guidance services effectively enhance self-awareness in high school students, aiding their career planning and decision-making. It is recommended to develop and update career guidance services to be more effective and tailored to students' career needs.